Correction of Skeletal Class II Malocclusion in a Growing Child Using Standard Twin Block: A Case Report - Kumar, Abhishek; Priya, Parul; Singh, Shresthaa; Jain, Abhay Kumar; Prasad, Raghu Ranjan (Orthodontic Journal of Nepal, 2023)
Mandibular defiiency in a Class II malocclusion is a frequently encountered condition that can be managed with myofunctional appliance in a growing child. An 11-year-old patient presented with a complaint of forwardly placed upper front teeth. The patient had a convex facial profie, acute naso-labial angle, deep mento-labial sulcus with lip trap. Clinically the patient showed positive VTO. The clinical fidings and cephalometric analysis indicated skeletal Class II jaw bases owing to prognathic maxilla and retrognathic mandible with Angle’s Class II division 1 malocclusion. CVMIshowed that the patient was in his growth phase. The treatment was done with a standard twin block appliance for 9 months followed by fied orthodontic treatment. The post functional phase showed correction of skeletal class II jaw base and marked improvement in the facial profie from convex to straight. It was later followed by fixed orthodontic treatment in the second phase upon completion of which bonded lingual retainer and wrap around retainers were given in the upper and lower arch. The total duration of the treatment was 23 months.